The Role of Entrepreneurial Mindset and Innovation in Enhancing Students’ Growth and Engagement - Emmanuela Nneka Clinton (CV. Tripe Konsultan, 2026)
This study examined the role of entrepreneurial mindset and innovation in enhancing students’ growth and engagement, focusing on higher education in Nigeria. Using a qualitative content analysis of 25 peer-reviewed papers published between 2015 and 2025, the study applied the PRISMA framework to ensure rigor and relevance. Findings revealed that an entrepreneurial mindset improved self-efficacy, motivation, and persistence, while innovation fostered creativity, problem-solving, and active engagement in learning. Importantly, the combined effect of mindset and innovation produced synergistic outcomes that significantly enhanced student growth and preparedness for post-graduation challenges. The study concludes that embedding entrepreneurial and innovative practices into university curricula is essential for addressing Nigeria’s educational and socio-economic gaps. Policy recommendations call for mandatory entrepreneurship-innovation modules, curriculum reforms, and institutional funding support to ensure sustainable student engagement and national development.